2006
DOI: 10.1152/ajpcell.00418.2005
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of JAK2 and Src kinase tyrosine phosphorylation in human growth hormone-stimulated increases in cytosolic free Ca2+ and insulin secretion

Abstract: GROWTH HORMONE (GH) is a major regulator of cell growth and metabolism. The actions of GH are the result of the interaction between GH and its receptors, which belong to the cytokine receptor superfamily. In rodent islet cells, effects of human (h)GH can also be mediated by the closely related prolactin (PRL) receptors (PRLRs). A significant characteristic of the cytokine receptor family is that the receptors do not contain intrinsic tyrosine kinase activity. Their transduction processes utilize nonreceptor ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 65 publications
1
17
1
Order By: Relevance
“…From this study we conclude that CCK-induced amylase secretion at either physiological, maximal, or supraphysiological concentrations is not SFK-dependent. This result differs from the SFK dependence of ␤-adrenergic agents to stimulate secretion from isolated rat salivary gland cells (73) or growth hormone to stimulate insulin release from pancreatic islets (92).…”
Section: Discussioncontrasting
confidence: 66%
“…From this study we conclude that CCK-induced amylase secretion at either physiological, maximal, or supraphysiological concentrations is not SFK-dependent. This result differs from the SFK dependence of ␤-adrenergic agents to stimulate secretion from isolated rat salivary gland cells (73) or growth hormone to stimulate insulin release from pancreatic islets (92).…”
Section: Discussioncontrasting
confidence: 66%
“…Previous studies in IM-9 and CHO cells based upon truncated and mutated GHR and JAK2 inhibitors had suggested that regulation of cellular [Ca 2+ ] by GH may also be JAK2 independent [21], raising the possibility that this function might also be mediated by Src. Although recent inhibitor studies by Zhang et al [29] found that human GH-induced increases in cytosolic free Ca 2+ in and insulin secretion from BRIN-BD11 beta cells appeared to be dependent upon activation of both JAK2 and Src, these actions were not mediated via the GHR but rather the prolactin receptor which can also bind human GH. In contrast, the rise in cytosolic free Ca 2+ elicited by bovine GH, which binds only to the GHR, was not blocked by inhibitors of either JAK2 or Src.…”
Section: Gh Signal Transduction Via Src Tyrosine Kinasementioning
confidence: 90%
“…Through its receptor, the growth hormone can also activate the intracellular signal paths independent of kinase JAK2 (Lanning, Carter-Su, 2006). An example is the participation of the growth hormone in the cellular calcium economy, taking place through the tyrosine kinase Src (Zhang et al, 2006). Transduction of the signal induced by GH is sometimes connected with the intracellular changes of the concentration of calcium ions and takes place through the calcium channels dependent on kinase PI3-K and activation of protein kinase C (PKC, Protein Kinase C) (Moutoussamy et al, 1998).…”
Section: Transduction Of the Signalmentioning
confidence: 99%